Halo gravity traction utilized in the treatment of early-onset scoliosis for patients with Prader-Willi Syndrome: A case report - Catherine M. Call; Bruce MacWilliams; Kristen Carroll; Joshua Klatt (Journal of Orthopaedic Reports)
Purpose: This report presents the cases of three pediatric patients with severe scoliosis and Prader-Willi Syndrome (PWS) who underwent halo gravity traction (HGT). Case report: A retrospective review of three children with PWS treated with HGT application followed by growth-sparing surgery was performed. All three patients were receiving growth hormone. Patient 1 aged 13 (BMI 29), patient 2 aged 6 (BMI 19), and patient 3 aged 8 (BMI 16) were treated with HGT applied for an average duration of 24 days. Following HGT and growth-sparing surgery, the coronal curve corrected in all patients while the sagittal curve progressed in two patients. There were no HGT complications and one surgical complication of transient intraoperative neurophysiological monitoring signal loss. Longer term follow-up (average 2.3 years) showed difficulty of maintained correction. All three patients tolerated HGT well. Conclusion: PWS is associated with musculoskeletal and behavioral traits that can impact scoliosis treatment planning. This report describes three patients with PWS safely treated with HGT prior to surgical intervention for severe scoliosis. HGT has been utilized for severe scoliosis to maximize preoperative health status and has been shown to decrease surgical risks by allowing for gradual curve correction. Augmentation of scoliosis treatment with HGT can be considered in patients with PWS.